IDENTIFIKASI MISKONSEPSI PESERTA DIDIK MENGGUNAKAN GOOGLE FORM PADA MATERI FLUIDA DINAMIS DI SMA KAPUAS PONTIANAK - Yuni Asnita; Stepanus Sahala Sitompul; Syaiful B. Arsyid (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2023)
This research focuses on students' misconceptions on dynamic fluid, especially on The Continuity Principle and Bernoulli’s Principle. The purpose is to identify students' misconceptions and the percentage of each student's misconceptions that are identified on the dynamic fluid by Google form at Kapuas Senior High School Pontianak. This research uses a quantitative research method with diagnostic tasks by Google form as a data collection tool. The objects were 24 students from class 12 on science major that were studied about dynamic fluid. Based on data analysis, the result is 5 students misconceptions identified are, Students assume the larger the cross-sectional area, the greater the fluid discharge, as much as 33.95%; Students consider the larger the cross-sectional area, the smaller the fluid discharge, as much as 9.72%; Students consider the fluid velocity to be directly proportional to the cross-sectional area, as much as 13.89%; Students consider the pressure to be inversely proportional to the cross-sectional area of the pipe, as much as 27.75%; Students consider the pressure to be directly proportional to the fluid velocity, as much as 2.77%.